The frequency and types of chromosomal abnormalities in leukemia (Experimental biology, 2015)
The paper presents the frequency and types of chromosomal aberrations in bone marrow cells in 19 children with leukemia. As a result of cytogenetic research to quantitative and structural features of chromosomal mutations, depending on the types of the disease. Numerical and structural chromosome aberrations were detected in 4 patients, the frequency of occurrence was 21.05%. Chromosomal aberrations were observed in 18 patients – 94.74%. By type of chromosomal aberration frequency was: translocation – 63.16%, deletions – 31.58%, marker chromosomes – 10.53%. The frequency of mosaic karyotypes options was 21.05%. In 2 patients with children of the same type installed chromosomal abnormalities involving 11 chromosome – del(11)(p14), the third patient also revealed a translocation involving chromosomes 11-th – t(11; 14)(p13; q11). In 3 patients a monotype translocation – t(8; 21)(q22; q22). Most rarely found in Western Europe and Russia mutation del(6)(q21) was observed in the patients examined at a frequency of 15.79%
Keywords: chromosome mutation; aberration; deletion; translocation; leukemia